Pengaruh Pendapatan Asli Daerah dan Belanja Modal terhadap Tingkat Kemandirian Keuangan Pemerintah Daerah Provinsi Sumatera Barat - Misra Sarumaha; Annisa Annisa (Universitas Katolik Widya Karya Malang, 2023)
This study aims to re-examine previous research between independent variables, namely local revenue and capital expenditure on financial independence. The object in this study is Financial Independence and the subject of this research is the Regional Government of West Sumatra Province for 2019-2021. The population in this study is the report on the realization of the budget revenues, capital expenditures and regional revenues of the Regional Government of West Sumatra Province. The type of data in this study uses a quantitative approach. The data source used is secondary data, namely data collected from existing records. This study took research samples using sensu techniques or saturated samples. The sample used in this study is the report on the realization of the APBD (Regional Revenue and Expenditure Budget) of the Regency/City Regional Government of West Sumatra Province which has been audited by the BPK with a total of 19 samples. The results of this study indicate that Regional Original Income has a positive effect on regional financial independence. Meanwhile, capital expenditure has a negative effect on regional financial independence.